Multi-wavelength light absorption of black and brown carbon at a high-altitude site on the Southeastern margin of the Tibetan Plateau, China. (1st September 2019) - Zhao, Zhuzi; Cao, Junji; Chow, Judith C.; Watson, John G.; Chen, Antony L-W.; Wang, Xiaoliang; Wang, Qiyuan; Tian, Jie; Shen, Zhenxing; Zhu, Chongshu; Liu, Suixin; Tao, Jun; et al.
Abstract: The Tibetan Plateau (TP) is one of the world's most sensitive areas for climate change, but the lack of information on light-absorption by aerosols limits the understanding of climate forcing feedbacks. Here, the contributions of black carbon (BC) and brown carbon (BrC) to light absorption and radiative forcing were investigated. Absorption Ångström exponents (α), mass absorption cross sections (MAC), and absorption coefficients ( b abs ) for selected wavelengths were measured for a year of aerosol samples collected at Lulang on the southeast TP. Aerosol absorption at all wavelengths was strongest in the pre-monsoon when levoglucosan, a biomass burning indicator, was elevated. The contributions of BC, BrC, and dust to b abs were decoupled. Results showed that dust contributed 8.5% to the total light absorption at 405 nm and 3.9% 808 nm. A two-component model indicated that BC and BrC contributed 48.7% and 44.0% to total b abs at 405 nm but BrC had a smaller effect at middle-visible wavelengths. Elevated b abs, non-dust, BC and b abs, non-dust, BrC and a high αBrC but low αaerosol values in the pre-monsoon were attributed to biomass burning, which produces not only BrC but also BC which has a much lower α value. Average non-dust MACs for BC and BrC at 405 nm were 6.1 ± 2.8 and 0.72 ± 0.55 m 2 g −1, respectively. Nonparametric statistical tests showed that the MACnon-dust, BC was relatively constant but MACnon-dust, BrC was more variable. In addition, BrC was correlated with non-dust b abs, BC and MACnon-dust, BC in winter and the pre-monsoon, implying BrC and BC shared sources in those two seasons, but lower correlations in the monsoon and post-monsoon suggest that a mixture of sources impacted BrC (e.g., biogenic emission, secondary formation, etc.). Finally, the relative contributions of BrC to BC for radiative forcing from 405 to 808 nm were 29.4 ± 9.5% with no remarkable seasonal differences, confirming the importance of BrC to light absorption in the near UV throughout the year. As a result, the BrC absorption is an important additional factor which needs to be considered in atmospheric models, although the atmospheric heating by BC seems to be a larger climate forcer in this region. Highlights: Filter-based measurement of light absorption from southeast TP were carried. Dust contributed 8.5% to total light absorption at 405 nm and 3.9% at 808 nm. BrC shared the same primary sources with BC in pre-monsoon and winter. MACnon-dust, BC was relatively constant while that for BrC was more variable. Averaged contribution of direct radiative forcing of BrC to that of BC was 29.4%.